The Effect of Job Satisfaction and Job Stress on Employee Performance PT. Primus Sanus Cooking Oil Industrial Karawang - Nandang, Nandang; Jamaludin, Asep; Hendi, Ujang (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to see any differences in the results of the effect of job satisfaction and job stress on employee performance at PT Primus Sanus Cooking Oil Industrial Karawang. In this study, quantitative methods were used to examine employee retention and work stress that affect employee performance at PT Primus Sanus Cooking Oil Industrial Karawang. The population in this study were employees of PT Primus Sanus Cooking Oil Industrial Karawang, while the sample taken was 72 respondents who were randomly selected using accidental sampling. . In this study, data analysis used multiple regression methods den R square. This study concluded that job satisfaction has a positive effect on employee performance, and job stress is proven to have a negative effect on employee performance. R square or the coefficient of determination produces a value of 0.369. This figure implies that the independent variable has an impact of 36.9% on the dependent variable, with the remaining 63.1% being influenced by other factors.